Fenomena “Anak Badut” di Kota Medan - Assingkily, Muhammad Shaleh; Sit, Masganti (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2020)
"Clown children" is a new entertainment for Medan City residents, especially children. This phenomenon arose along with the Covid-19 pandemic and was mostly played by young children on the pretext of hoping for people's compassion, to be precise as of August 2020. Even though before the Covid-19 pandemic there were already "clowns" on the streets, but there were more characters. adults. Various factors led to the emergence of "clown children" with the role of young children in Medan. This paper aims to analyze the phenomenon of the emergence of "clown children" in the Covid-19 era in Medan, which is played by early childhood, which is researched using a qualitative approach using phenomenological study methods. Data were collected by means of interview, observation and document review techniques. Furthermore, data reduction, data display or presentation and drawing conclusions are performed as a form of data analysis. The results of this study indicate that the “clown boy” played by early childhood children on the streets of Medan is caused by 3 (three) factors, namely making money, helping parents and filling spare time due to the Covid-19 pandemic.